META-ANALYSIS STUDY: EFFECT OF REALISTIC MATHEMATICS EDUCATION APPROACH ON STUDENT'S MATHEMATICAL LITERACY ABILITY - Chelsi Ariati; Vera Anzani; Dadang Juandi; Aan Hasanah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
A comprehensive review about approach to Realistic Mathematics Education (RME) impact on mathematical literacy abilities has not been studied extensively, consequently, many teachers are unaware of the advantages of this method for students. This meta-analysis research was carried out to analyze the overall effect size of applying the RME approach to mathematical literacy skills. Empirical data obtained from Google Scholar, Semantic Scholar, URL link directly. The outcomes of the search are nine articles published between 2016 and 2021. In accordance with the inclusion criteria, nine items were qualified for analysis. Comprehensive Meta-Analysis (CMA) software is used in the analysis tool, and a random estimation model. The results revealed that the study's overall effect size was 1.051. These findings suggest that the application of the RME approach has a strong effect on students' mathematical literacy abilities. The moderator variables were examined, and it was discovered that the RME approach was effective by considering student demographics, but not at the educational level. This meta-analysis study advises Indonesian math teachers that the application of RME in increasing students' mathematical literacy should be used more frequently, especially in elementary schools.Ulasan komprehensif tentang efek dari pendekatan Realistic Mathematics Education (RME) pada kemampuan literasi matematis belum banyak dipelajari secara ekstensif, menyebabkan banyak guru yang belum menyadari manfaat dari pendekatan ini untuk siswa. Studi meta-analisis ini dilakukan untuk menganalisis ukuran efek keseluruhan penerapan pendekatan RME terhadap kemampuan literasi matematis. Data empiris diperoleh dari Google Scholar, Semantic Scholar, Link URL secara langsung. Hasil pencarian menemukan sembilan artikel diterbitkan antara 2016 dan 2021. Menurut kriteria inklusi, sembilan item memenuhi syarat untuk analisis. Alat analisis menggunakan perangkat lunak Comprehensive Meta-Analysis (CMA), dan model estimasi random. Hasil penelitian mengungkapkan bahwa ukuran efek keseluruhan dari penelitian ini adalah 1,051. Hasil ini menunjukkan bahwa penerapan pendekatan RME memiliki efek kuat pada kemampuan literasi matematis siswa. Analisis variabel moderator mengungkapkan bahwa Pendekatan RME pelaksanaannya efektif dengan mempertimbangkan demografi siswa, namun tidak pada tingkat pendidikan. Studi meta-analisis ini merekomendasikan kepada guru matematika Indonesia agar penerapan RME dalam meningkatkan literasi matematika siswa harus lebih diterapkan terutama di sekolah dasar.